2010
DOI: 10.1371/journal.pone.0015875
|View full text |Cite|
|
Sign up to set email alerts
|

Alzheimer's Aβ Peptides with Disease-Associated N-Terminal Modifications: Influence of Isomerisation, Truncation and Mutation on Cu2+ Coordination

Abstract: BackgroundThe amyloid-β (Aβ) peptide is the primary component of the extracellular senile plaques characteristic of Alzheimer's disease (AD). The metals hypothesis implicates redox-active copper ions in the pathogenesis of AD and the Cu2+ coordination of various Aβ peptides has been widely studied. A number of disease-associated modifications involving the first 3 residues are known, including isomerisation, mutation, truncation and cyclisation, but are yet to be characterised in detail. In particular, Aβ in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
88
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(95 citation statements)
references
References 67 publications
6
88
1
Order By: Relevance
“…pE-A␤ peptides also demonstrate increased ␤-sheet (aggregate structure) stability (16,17), differences in fibril ultrastructure (18,19), and altered interactions with copper ions (20,21) and synthetic lipid membranes (22,23). Notably, trace quantities of A␤3pE-42 have been observed to dramatically enhance the aggregation and neurotoxicity of A␤ (24), prompting descriptions of pE-A␤ as "prionlike."…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…pE-A␤ peptides also demonstrate increased ␤-sheet (aggregate structure) stability (16,17), differences in fibril ultrastructure (18,19), and altered interactions with copper ions (20,21) and synthetic lipid membranes (22,23). Notably, trace quantities of A␤3pE-42 have been observed to dramatically enhance the aggregation and neurotoxicity of A␤ (24), prompting descriptions of pE-A␤ as "prionlike."…”
mentioning
confidence: 99%
“…Imbalances in ROS production and detoxification are strongly implicated in AD neurodegeneration, reflected by cerebral elevations in oxidized DNA, lipids, and proteins (35)(36)(37). Pyroglutamate formation alters A␤-Cu 2ϩ coordination modes (20,21), although it is not known whether this affects the capacity of pE-A␤ peptides to undertake redox cycling and produce cytotoxic ROS. We therefore aimed to determine whether full-length A␤ and pE-A␤ possess differences in their capacity to alter ROS flux and cause oxidative damage to neurons in vitro.…”
mentioning
confidence: 99%
“…Other modifications include metal-induced oxidation (23) or phosphorylation (24,25). In general, N-terminal modifications significantly influence the Cu 2ϩ coordination of A␤, which may be critical for alterations in aggregation propensity, redox activity, and resistance to degradation (26). In addition, it has been shown that certain apolipoprotein E isoforms bind to A␤ and with less avidity to modified species, including isomerized and pyroglutamate-modified A␤ (A␤ pE3 ) (27).…”
mentioning
confidence: 99%
“…More generally, N-terminally truncated peptides might also be considered for new therapeutic targets. [9] To conclude, and as previously pointed out in seminal works, [103,104,111,134,136] the interaction of Cu II with N-terminally truncated peptides might reshape our current view of the deleterious impact of Cu II binding to amyloid-peptides.…”
Section: Resultsmentioning
confidence: 54%
“…[9] The formation of the A 11-40/42 peptide is due to the activity of a secondary -secretase ( ′). 0.12 [134,136] [a] A s parameters refer to 63 Cu.…”
Section: Amino-terminal Copper and Nickel (Atcun) Type Motifsmentioning
confidence: 99%